2022
DOI: 10.1210/clinem/dgac067
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Due to Steroid Receptor Coactivator-1 Deficiency Is Associated With Endocrine and Metabolic Abnormalities

Abstract: Context Genetic variants affecting the nuclear hormone receptor coactivator Steroid Receptor Coactivator, SRC-1, have been identified in people with severe obesity and impair melanocortin signaling in cells and mice. As a result, obese patients with SRC-1 deficiency are being treated with a Melanocortin 4 receptor agonist in clinical trials. Objective Here, our aim was to comprehensively describe and characterise the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Variants in ≥1 gene and/or chromosomal deletion with a strong effect [ 56 , [85] , [86] , [87] , [88] , [89] , [90] ]…”
Section: Differentiating Characteristics Of Polygenic Monogenic and S...mentioning
confidence: 99%
“…Variants in ≥1 gene and/or chromosomal deletion with a strong effect [ 56 , [85] , [86] , [87] , [88] , [89] , [90] ]…”
Section: Differentiating Characteristics Of Polygenic Monogenic and S...mentioning
confidence: 99%
“…Steroid receptor coactivator-1 (SRC1) affects the expression of many target genes [52]. In a previous large exome-sequencing study of patients with severe obesity, rare heterozygous variants in SRC1 were detected and were associated with the dysregulation of POMC expression [53,54]. Importantly, SRC-1 deletion also caused obesity in mice [55].…”
Section: Src1 Deficiencymentioning
confidence: 99%
“…In a recent study, it was shown that in the hypothalamus, SRC-1 interacts with phosphorylated signal transducer and activator of transcription-3 (STAT3), affecting POMC expression [56]. Patients with SRC1 mutations and severe obesity have been enrolled in phase 2 clinical trials of setmelanotide, an MC4R agonist, approved for obese patients with POMC or LEPR mutations [54].…”
Section: Src1 Deficiencymentioning
confidence: 99%
“…Other genes are also implicated in the regulation of this pathway including MRAP2 encoding for the melanocortin receptor accessory protein 2 ( 8 , 9 ), ADCY3 encoding for adenylate cyclase 3 which transmits the MC4R activation signal intracellularly ( 10 ). Several genes involved in development of the hypothalamus or MC4R regulation have been reported to influence this signaling, including semaphorin 3A-G ( SEMA3A-G), plexinA1–4 ( PLXNA1–4 ), neuropilin1–2 ( NRP1–2 ) ( 11 ), kinase suppressor of ras 2 ( KSR2 ) ( 12 ), and the steroid-receptor co-activator 1 ( SRC-1 ) ( 13 ). Genetic alterations in these genes lead to the phenotype described in both monogenic obesity and also in syndromic obesity.…”
Section: Clinical Features Of Genetic and Syndromic Obesitiesmentioning
confidence: 99%